Advancements in silica-based nanostructured photocatalysts for efficient hydrogen generation from water splitting - Abdulkadir, B. A.; Teh, L. P.; Sumaiya, Zainal Abidin; Herma Dina, Setiabudi; Rohayu, Jusoh (Elsevier Ltd, 2023)
The development of effective catalysts, particularly silica-based nanostructured photocatalysts for hydrogen production via water splitting, has recently appeared as a research flashpoint. Although much progress has been made, basic issues are yet to be resolved to understand the relationship between the photocatalyst properties and the photocatalytic performance of silica-based nanostructured materials. Additionally, no article critically discusses the relationship of structures, types, properties, and metal-support interaction on photocatalytic performance. Therefore, this article provides an in-depth review of the recent advancements in silica-based nanostructured photocatalysts covering photocatalyst preparation methods and governing factors affecting hydrogen production. The role of metals, sacrificial reagents, supports, and metal-support interfaces in enhancing hydrogen production was comprehensively reviewed. Moreover, future prospects and opportunities for hydrogen production via water-splitting were also discussed. This article is anticipated to serve as an eye-opening point for future researchers interested in the creation of silica-based photocatalysts.